Attendance Web for Student Internships Using SAW - Dhany, Hanna Willa (Journal of Technology and Computer, 2024)
This study aims to design and implement a web-based attendance system for student interns using the Simple Additive Weighting (SAW) method. This system was developed to improve the efficiency and accuracy of attendance recording, as well as providing objective and transparent assessments based on predetermined criteria. The research method used is descriptive with a quantitative approach, including data collection through literature studies, observations, and interviews. The results of the study indicate that this web-based attendance system has succeeded in improving the efficiency and accuracy of attendance recording compared to manual methods. Functional and user testing shows that this system is easy to use and meets user needs. The SAW method applied in this system allows for more objective and transparent attendance assessments. With this system, educational institutions and companies can better monitor and evaluate the performance of student interns, so that it is expected to improve the quality of the internship program.